2008
DOI: 10.1681/asn.2007030289
|View full text |Cite
|
Sign up to set email alerts
|

Roles of ERK and cPLA2 in the Angiotensin II-Mediated Biphasic Regulation of Na+-HCO3 − Transport

Abstract: Regulation of renal proximal transport by angiotensin II (Ang II) is biphasic: low concentrations (picomolar to nanomolar) stimulate reabsorption, but higher concentrations (nanomolar to micromolar) inhibit reabsorption. Traditionally, the stimulatory effect has been attributed to activation of protein kinase C and/or a decrease in intracellular cAMP, whereas the inhibitory action has been attributed to the activation of phospholipase A 2 (PLA 2 ) and the subsequent release of arachidonic acid. The Ang II rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
64
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 41 publications
(82 reference statements)
10
64
0
1
Order By: Relevance
“…On the other hand, the MEK inhibitor PD9805 abolished only the stimulatory effect of Ang II, leaving the inhibitory effect of Ang II unaffected. These results indicate that the ERK pathway mediates only the stimulatory effect of Ang II in intact proximal tubules [12]. Further analysis showed that the inhibitory effect of Ang II is independent of the ERK pathway, but dependent on the group IVA cytosolic PLA 2 (cPLA2 ) activity.…”
Section: Erk Pathway In Ang II Actions On Renal Proximal Transportmentioning
confidence: 87%
See 1 more Smart Citation
“…On the other hand, the MEK inhibitor PD9805 abolished only the stimulatory effect of Ang II, leaving the inhibitory effect of Ang II unaffected. These results indicate that the ERK pathway mediates only the stimulatory effect of Ang II in intact proximal tubules [12]. Further analysis showed that the inhibitory effect of Ang II is independent of the ERK pathway, but dependent on the group IVA cytosolic PLA 2 (cPLA2 ) activity.…”
Section: Erk Pathway In Ang II Actions On Renal Proximal Transportmentioning
confidence: 87%
“…The recent study has shown that the ERK pathway is also involved in the Ang IImediated stimulation of sodium absorption from renal proximal tubules [12]. However, Ang II seems to utilize quite different signaling mechanisms to activate ERK in VSMCs and renal tubules.…”
Section: Introductionmentioning
confidence: 99%
“…Although controversial data have been reported concerning the receptor subtype(s) that are responsible for the biphasic effects of ANG II on proximal tubular transport [87,88], some studies have clearly indicated that both luminal and basolateral AT1A receptors mediate the biphasic effects of Ang II on proximal transport [89][90][91]. It has been shown that at physiological concentrations, binding between ANG II and the AT1 receptor induces the rapid activation of PLC, which results in the release of IP3 and DAG, which are themselves involved in slightly increasing [Ca 2+ ]i by mobilizing Ca 2+ from intracellular storage and by activating PKC, respectively [92][93][94].…”
Section: Dose-dependent Biphasic Effects Of Ang II In the Proximal Tumentioning
confidence: 99%
“…It has been shown that at physiological concentrations, binding between ANG II and the AT1 receptor induces the rapid activation of PLC, which results in the release of IP3 and DAG, which are themselves involved in slightly increasing [Ca 2+ ]i by mobilizing Ca 2+ from intracellular storage and by activating PKC, respectively [92][93][94]. These processes may ultimately result in the activation of ERK [71,83,90]. At high concentrations, ANG II induces the activation of the phospholipase A2 (PLA2)/arachidonic acid/5,6-epoxyeicosatrienoic acid (EET) pathway and/or the NO/ cGMP pathway and the mobilization of intracellular Ca 2+ , also through mechanisms involving the AT1 receptor [83,86,95,96].…”
Section: Dose-dependent Biphasic Effects Of Ang II In the Proximal Tumentioning
confidence: 99%
See 1 more Smart Citation